It takes three to the DNA damage response tango. (4th March 2021) - Schlam-Babayov, Sapir; Ziv, Yael; Shiloh, Yosef
ABSTRACT: The DNA damage response is robustly activated by DNA double-strand breaks and controlled by three apical protein kinases of the PI3-kinase-related protein kinase (PIKK) family: ataxia-telangiectasia, mutated (ATM), ataxia-telangiectasia and Rad3-related (ATR) and DNA-dependent protein kinase (DNA-PK). Phosphoproteomic analysis reveals the relative share of these PIKKs in coordinating this network, and compensation by ATR and DNA-PK for ATM absence in the genetic disorder, ataxia-telangiectasia (A-T).